Odpowiedź:
Szczegółowe wyjaśnienie:
4 2/5 - 6 1/4 = (4 + 2/5) - (6 + 1/4) =
= (80/20 + 8/20) - (120/20 + 5/20) =
= 88/20 - 125/20 = - 37/20 = - 20/20 - 17/20 = - 1 - 17/20 =
= - 1 17/20 = - 1 i 17/20 (minus 1 cała i 17/20
- 2 1/5 + 3 1/3 = - (30/15 + 3/15) + (45/15 3/15) = - 33/15 + 48/15 =
= 15/15 = 1
- 4 1/2 - 2 1/4 = - 16/4 - 2/4 - 8/4 - 1/4 = 27/4 = 24/4 + 3/4 = 6 3/4 = 6 i 3/4
- 5 4/7 + 7 = - 35/7 - 4/7 + 7 = - 5 + 7 - 4/7 =
= 2 - 4/7 = 14/7 - 4/7 = 10/7 = 7/7 + 3/7 = 1 + 3/7 = 1 3/7 = 1 i 3/7
- 5 - (- 2 + 9) = - 5 - 7 = - 12
- 7 - (- 14 - 3 + 5) = - 7 - (- 12) = - 7 + 12 = 5
- 6,2 + 3 = - 3,2
- 7 - (- 1,2 + 8) = - 7 - (6,8) = - 13,8